Analysis of chlortetracycline by high performance liquid chromatography with postcolumn alkaline-induced fluorescence detection - Capomacchia, Anthony C. (1992)
A high performance liquid chromatographic method for the analysis of chlortetracycline (CTC) using postcolumn fluorescence detection has been developed. After chromatographic separation of CTC on a polystyrenedivinylbenzene copolymer column, a highly fluorescent derivative isochlortetracycline (iso-CTC) was formed postcolumn in an on-line reaction coil with the addition of 25% NaOH (w/v). Chromatographic separation was achieved on a PRP-1 column, 15 cm × 4.6 mm, with 27:73 acetonitrile:0.2% perchloric acid (v/v), at 1.0 mL/min. Fluorescence derivatization was achieved by the on-line addition of 25% NaOH (w/v), at a flow rate of 0.2 mL/min, into the column eluant in a post-column reaction coil. The reaction coil was 9 m of teflon (1/16 in o.d., 0.3 mm i.d.) knitted into a six-sided coil. The fluorescent derivative was detected at λex 355 nm and λem >389 nm. Using this method after a simple sample cleanup, CTC can be detected in milk at 0.04 μg/mL, which is comparable to that obtained by microbiological assays. The detection method was linear between 0.02 μg/mL and 4 μg/mL. Because of the chromatographic separation, the method is more selective than microbiological assays and more sensitive than ultraviolet detection. With the chromatographic system described, the keto tautomeric forms of CTC and 4-epi-CTC are separated in a system which minimizes their formation on-column. In acidic aqueous organic solutions, the keto tautomer of CTC is the only product formed to any significant amount.